Re-envisioning the Kimberley Mine Museum:De Beers’ Big Hole Project - Brown, Marj (My University, 2006)
The diamond company De Beers is in the process of re-designing the Kimberley Mine Museum – a site marking the very beginnings of South Africa’s industrial history. The development of the new attraction will be subject to various forces and considerations which will impact on how the museum will reflect the history of the city, of its people, and of De Beers itself. These forces include the traditional educational function of a museum, the historical functions of displaying social history, possible new political expectations of a more inclusive social history being displayed, the corporate ownership of this attraction, and commercial pressures. The main aim of the research will be to investigate ways in which an inclusive social history is accommodated in the planning process for the new museum.
Master of Arts in Heritage - Heritage Studies
Keywords: big hole; museum; de beers